Perjalanan Panjang Paṭola Menjadi Jlamprang: Transformasi Motif Tenun Menjadi Motif Batik - Siti Maziyah; Alamsyah Alamsyah (KALPATARU, 2021)
The background of this research comes from the public's understanding that the jlamprang motif is a typical Pekalongan batik motif, besides that there are also those who state that this motif is an imitation of the paṭola motif. Therefore, this paper aims to determine the transformation process of the patola woven motif into the jlamprang batik motif, one of the characteristic batik motifs of Pekalongan. Why can the weaving motif turn into a batik motif? Why does the jlamprang batik motif become the hallmark of Pekalongan? The method used in this research is to trace the trade of paṭola motif cloth from India and its distribution in Java, both in the form of the distribution of decorative motifs on temples and on cloth. The search was carried out through literary texts, decorative motifs on temple walls, and motifs of cloth worn by statues. The results showed that in Java the paṭola motif has undergone a transformation from a woven motif to a decorative motif on the temple walls to a batik motif. Jlamprang became the signature batik motif of Pekalongan because it was in this city that the motif was first developed by Arab traders to overcome the scarcity of paṭola woven motifs from India. Thus, it can be concluded that the Javanese society is an adaptive society, with local genius capable of processing foreign decorative motifs into their own motifs and making them a local identity.